2014
DOI: 10.2967/jnumed.114.140137
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Radiation Dosimetry of LMI1195: First-in-Human Study of a Novel 18F-Labeled Tracer for Imaging Myocardial Innervation

Abstract: A novel 18 F-labeled ligand for the norepinephrine transporter (N-[3-bromo-4-(3-18 F-fluoro-propoxy)-benzyl]-guanidine [LMI1195]) is in clinical development for mapping cardiac nerve terminals in vivo using PET. Human safety, whole-organ biodistribution, and radiation dosimetry of LMI1195 were evaluated in a phase 1 clinical trial. Methods: Twelve healthy subjects at 3 clinical sites were injected intravenously with 150-250 MBq of LMI1195. Dynamic PET images were obtained over the heart for 10 min, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…Desipramine added into the perfusion buffer markedly reduced the extraction to 4% at 4 mL/min/g. Furthermore, in vivo PET studies have confirmed the high contrast of 18 F-LMI1195 cardiac uptake in rabbits, monkeys, and humans (4,5). Notably, the specific neural transport observed in these species is not the same as seen in small rodents (16,17).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Desipramine added into the perfusion buffer markedly reduced the extraction to 4% at 4 mL/min/g. Furthermore, in vivo PET studies have confirmed the high contrast of 18 F-LMI1195 cardiac uptake in rabbits, monkeys, and humans (4,5). Notably, the specific neural transport observed in these species is not the same as seen in small rodents (16,17).…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, minimal liver uptake in comparison to other conventional nerve tracers was suggested in the animal experiments and is preferable for assessment of the left ventricular inferior wall. Most recently, a human volunteer study (clinical phase I trial) with 18 F-LMI1195 demonstrated promising clinical results, with uniform myocardial tracer uptake in the left ventricular wall and acceptable radiation exposure (5). Further mechanistic details of 18 F-LMI1195 cardiac retention are not yet fully elucidated.…”
mentioning
confidence: 99%
“…The results of imaging studies in rats, rabbits and non-human primates suggested that [ 18 F]FPOBBG (LMI1195) was a promising agent for PET imaging of cardiac sympathetic neuronal function [31] and a phase I clinical evaluation of this agent has been reported recently [37]. Although our evaluation [ 18 F]FPOIBG indicated it be not up to the par with MIBG (see below), we wondered whether its biological properties will be comparable to that of [ 18 F]FPOBBG.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the need for a nearby cyclotron makes 11 C-HED impractical for most practitioners. 18 F compounds that are more practical (e.g., 18 F-LMI-1195 (flurobenzylguanidine)) are under investigation [68].…”
Section: Tomographic Adrenergic Imaging and Arrhythmic Eventsmentioning
confidence: 99%